The Influence of Affection, Worklife Balance and Workload on the Welfare of Gen Z Female Employees in a Shoe Factory - Isnaeni, Lina; Puspita, Sindi; Siddiq, Dedi Muhammad; Setapa, Mariam (Jurnal Ekonomi dan Bisnis Digital, 2025)
Analyzing the effects of workload, work-life balance, and compassion on the wellbeing of female Generation Z workers in a shoe factory is the goal of this study.  This study's backdrop includes the high physical and emotional pressures Gen Z female employees confront, as well as the need for emotional support and work-life balance.  Several linear regression analyses were employed in a quantitative manner.  SPSS 25 was used to process the data once it was gathered via surveys. The findings demonstrated that workload significantly impacted employee well-being negatively, while compassion and work-life balance significantly improved it.  These results demonstrate the significance of cultivating a compassionate and encouraging workplace culture in order to sustainably enhance employee well-being.